Nakajo–Nishimura syndrome and related proteasome-associated autoinflammatory syndromes - Ohmura K (Dove Medical Press, 2019)
Koichiro Ohmura Department of Rheumatology and Clinical Immunology, Kyoto University Graduate School of Medicine, Kyoto 606-8507, JapanCorrespondence: Koichiro OhmuraDepartment of Rheumatology and Clinical Immunology, Kyoto University Graduate School of Medicine, 54 Kawahara-cho, Shogoin, Sakyo-ku, Kyoto 606-8507, JapanTel +81 75 751 4380Fax +81 75 751 4338Email ohmurako@kuhp.kyoto-u.ac.jpAbstract: Nakajo–Nishimura syndrome (NNS) is a rare hereditary autoinflammatory disorder with lipodystrophy. This disease is caused by a homozygous mutation of PSMB8 gene, which encodes immunoproteasome subunit β5i. Phenotypes of NNS patients are periodic fever, pernio-like rash, nodular erythema-like eruptions, and lipomuscular dystrophy, especially in the upper body, leading to the characteristic long, clubbed fingers. NNS was considered to be endemic to the Kansai area of Japan, but patients with similar phenotypes and the mutation of PSMB8 gene were reported in other countries, and named Chronic atypical neutrophilic dermatosis with lipodystrophy and elevated temperature (CANDLE) syndrome and joint contractures, muscular atrophy, microcytic anemia, and panniculitis-associated lipodystrophy (JMP) syndrome. These syndromes are now called proteasome-associated autoinflammatory syndromes (PRAASs), and their main pathophysiological mechanism seems to be interferonopathy. In this review, the history, characteristics, and the pathophysiological mechanism of PRAASs will be discussed, focusing mainly on NNS.Keywords: Nakajo-Nishimura syndrome, PSMB8, autoinflammatory syndrome, proteasome, lipodystrophy, interferonopathy